MENENTUKAN SEGMEN PASAR MELALUI PENGENALAN PRODUK BAGI PELAKU USAHA - Eni Widhajati; Desi Rahmawati; Latifatul Isroiyah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Tulungagung, 2024)
The importance of business actors in increasing economic growth for a country makes it a shared task to develop business actors in Indonesia. By helping business actors to increase market segments through product introduction, it can increase sales for business actors so that economic growth increases and has an impact on the welfare, security, and progress of a country. The existence of business actors can absorb labor and reduce unemployment and poverty and improve the welfare of community members. For that, through this activity, it is expected that new business actors who develop and grow through it can help to increase their sales through activities to determine market segments and introduce new products to determine strategies so that market targets can be increased, and sales will also increase. This is expected to be able to find out consumer needs and problems, know consumer behavior, analyze data, determine marketing strategies, and evaluate market responses. Thus, it is important to note that business actors can carry out their business in accordance with the type of business and the position of the business actor at what stage so that they can choose the strategy used and how product introduction can be carried out to consumers.